Fluorite and translucent beads in Iberian Late Prehistory - Garrido-Cordero, José Ángel (2020)
This paper is a research contribution about translucent beads, with special attention to fluorite mineral used by the communities of Iberian Late Prehistory. We review the use and social significance of translucent beads in this period. The starting point for this study is the chemical (Raman spectroscopy, p-XRF, XRD and VIS/NIR) and contextual analysis of an important number of adornments inventoried here for the first time, as well as a review of archeological literature on transparent/translucent beads.